Effects of thinning on growth and development of second poplar generations - Nguyen, Thi Ha (SLU/Southern Swedish Forest Research Centre, 2018)
Stands consisting of poplar stump sprouts and root suckers show high potential of successful establishment and pose a cheap management alternative to the currently planted poplar plantations. Due to the relatively small proportion of presently existing poplar plantations in Sweden, especially second generations, knowledge about production potential and silviculture treatments for poplar is scarce. Thus, this study focused on investigating production potential and response of poplar second generations to thinning treatments under the following 3 hypotheses, namely: (1) Stump sprouts are dominant in stands of poplar sprouts and root suckers, (2) Thinning increases volume production (3) Thinning improves stem growth, production, and stem stability of crop trees.